Organização e politização do movimento de saúde dos portadores falcêmicos na grande São Paulo - Brasil - Araújo, Reginaldo Silva de (Universidade Federal de São Carlos, 2004)
The principal aim of this research is to look for the normative and political construction of illnesses considered ethnic specific, such as the sickle cell anemia, in the scope of the movements and forms of organization which are representative of certain population groups (in the case, the black movement), as well as in the scope of the politics of public health programs for the attendance of the population that presents the trace of the referring hemoglobin or the proper sickle cell anemia illness. It intends also to study the associations of the Black Movement and the Movement of Specific Illnesses (sickle cell anemia) as they are politically organized and constructing claims together with the governmental services for the attendance of particular demands of health for specific population groups, as it is the case of the preventive care and attention to the health of the carrying patients of the sickle cell anemia. It searches, thus, to know how these movements are interrelated and how they prioritize the guidelines to the improvement of care for the carriers of the sickle cell anemia. The analysis of these forms of organization and political performance would still look for to observe how the construction of the sickle cell anemia as "ethnic illness" or "specific illness" can be an instrument not only for the claims of some population groups towards a specific health care service, but also in which way the proper notion of "ethnic illness" or "specific illness" can become, eventually, a normative construction related to certain political mottos, such as "citizenship" or "racial democracy".
Keywords: Antropologia; Antropologia da saúde; Movimentos sociais; Movimento negro; Anemia falciforme; Doenças étnicas; Doença específica; Social movements; Black movement; Sickle cell anemia; Ethnic illness; Specific illness; CIENCIAS HUMANAS::ANTROPOLOGIA